Spinal dermal sinus coinciding with an infected giant epidermoid cyst in an infant presenting with constipation: a case report - Mohamad Saekhu; Eka Susanto; Setyo Handryastuti; Samsul Ashari; Setyowidi Nugroho (Indonesian Pediatric Society, 2022)
Early diagnosis of spinal tumors is a prerequisite for achieving satisfactory neurological recovery. However, rare diseases tend to have a long diagnostic course.1 In addition, the clinical presentation of spinal tumors in most children is not apparent, moreover, spinal tumors may not show clinical symptoms if they are located in the lumbar spine and sized no more than one vertebra.2,3 Clinical presentations caused by tumors in the lumbar spine may include weakness of both limbs, impaired urination, and constipation.